European women in neurosurgery: II – Historical characters and living legends. (April 2021) - Murphy, Mary; Hernández-Durán, Silvia; Kim, Eliana; Al-Shehhi, Noora; Broekman, Marike; de Praeter, Mania; Dubuisson, Annie; Emery, Évelyne; Gazioglu, Nurperi; Grossman, Rachel; Janssen, Insa Katrin; Karampouga, Maria; et al.
Highlights: The leitmotif of women in European neurosurgery is resilience and ingenuity. Female neurosurgeons in Europe have been humanitarians and politicians. Beyond the operating room, women in European neurosurgery have excelled in many fields. Abstract: A collaborative global working group of women neurosurgeons in multiple countries at different stages of their neurosurgical careers undertook the task of researching the history of European women in neurosurgery. While doing so, we happened upon many remarkable female neurosurgeons who overcame great adversity, made tremendous contributions to society and institutional neurosurgery, and displayed numerous talents beyond the operating room. In the first part of this paper, we recounted a chronology of female neurosurgeons in Europe, highlighting the most remarkable achievements of women in every decade, from the 1920's to 2020. In this paper, we honor fascinating women in European neurosurgery, both historical characters and living legends. These women have overcome great adversity and have also excelled in a huge variety of pursuits. While some were themselves refugees, we also have uncovered noteworthy examples of women who immersed themselves in humanitarian missions and who tried to better the world through political action. There are stories of women beating the odds, taking on biased institutions and proving their worth, in spite of the prevailing system. Most inspirational, we have discovered through our comprehensive research on the history of women in European neurosurgery that the future is increasingly female.